Carbapenemase production among less-common Enterobacterales genera: 10 US sites, 2018. Issue 3 (4th September 2021) - Shugart, Alicia; Mahon, Garrett; Huang, Jennifer Y; Karlsson, Maria; Valley, Ann; Lasure, Megan; Gross, Annastasia; Pattee, Brittany; Vaeth, Elisabeth; Brooks, Richard; Maruca, Tyler; Dominguez, Catherine E; et al.
Abstract: Background: Historically, United States' carbapenem-resistant Enterobacterales (CRE) surveillance and mechanism testing focused on three genera: Escherichia, Klebsiella, and Enterobacter (EsKE); however, other genera can harbour mobile carbapenemases associated with CRE spread. Objectives: From January through May 2018, we conducted a 10 state evaluation to assess the contribution of less common genera (LCG) to carbapenemase-producing (CP) CRE. Methods: State public health laboratories (SPHLs) requested participating clinical laboratories submit all Enterobacterales from all specimen sources during the surveillance period that were resistant to any carbapenem (Morganellaceae required resistance to doripenem, ertapenem, or meropenem) or were CP based on phenotypic or genotypic testing at the clinical laboratory. SPHLs performed species identification, phenotypic carbapenemase production testing, and molecular testing for carbapenemases to identify CP-CRE. Isolates were categorized as CP if they demonstrated phenotypic carbapenemase production and ≥1 carbapenemase gene ( bla KPC, bla NDM, bla VIM, bla IMP, or bla OXA-48-like ) was detected. Results: SPHLs tested 868 CRE isolates, 127 (14.6%) were from eight LCG. Overall, 195 (26.3%) EsKE isolates were CP-CRE, compared with 24 (18.9%) LCG isolates. LCG accounted for 24 (11.0%) of 219 CP-CRE identified. Citrobacter spp. was the most common CP-LCG; the proportion of Citrobacter that were CP (11/42, 26.2%) was similar to the proportion of EsKE that were CP (195/741, 26.3%). Five of 24 (20.8%) CP-LCG had a carbapenemase gene other than bla KPC . Conclusions: Participating sites would have missed approximately 1 in 10 CP-CRE if isolate submission had been limited to EsKE genera. Expanding mechanism testing to additional genera could improve detection and prevention efforts.